Return to the Moon Exploration, Enterprise, and Energy in the Human Settlement of Space - Schmitt, Harrison (Springer New York : Imprint: Copernicus, 2006)
Former NASA Astronaut Harrison Schmitt advocates a private, investor-based approach to returning humans to the Moon-to extract Helium 3 for energy production, to use the Moon as a platform for science and manufacturing, and to establish permanent human colonies there in a kind of stepping stone community on the way to deeper space. With governments playing a supporting role-just as they have in the development of modern commercial aeronautics and agricultural production-Schmitt believes that a fundamentally private enterprise is the only type of organization capable of sustaining such an effort and, eventually, even making it pay off.